2019
DOI: 10.1248/bpb.b18-00979
|View full text |Cite
|
Sign up to set email alerts
|

Olive-Derived Hydroxytyrosol Shows Anti-inflammatory Effect without Gastric Damage in Rats

Abstract: Hydroxytyrosol (HT) is a simple phenol compound present in olive oil. In a previous in vitro study, we showed that HT downregulated lipopolysaccharide-mediated expression of inducible nitric oxide synthase, cyclooxygenase-2 (COX-2), tumor necrosis factor alpha, and interleukin-1β, resulting in reduced nitric oxide and prostaglandin E 2 production. In the present study, we aimed to determine whether HT suppresses COX-2-induced inflammation in a carrageenan-induced rat paw edema model. Additionally, we compared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 30 publications
1
9
0
Order By: Relevance
“…HT-29 intestinal cells 1-5 µg/mL Induction of apoptosis through COX-2 suppression and AMPK activation [122] Oleuropein showed an inhibitory effect against COX-2 over-expression in different tumor cell lines [130], but the most studied EVOO phenolic compound is undoubtedly its derivative HT. It was shown, for instance, that LPS-induced expression of COX-2 and thus PGE2 production were inhibited by HT pretreatment in human and mouse granulocytes, macrophages, and monocytes [66,100,[124][125][126][127]. Among the mechanisms involved in COX-2 suppression by HT, as well as by EVOO polyphenols extracts, the inhibition of NF-κB following MAPKs modulation is the most recognized [107].…”
Section: Inhibition Of Cox-2 and Prostaglandinsmentioning
confidence: 99%
See 1 more Smart Citation
“…HT-29 intestinal cells 1-5 µg/mL Induction of apoptosis through COX-2 suppression and AMPK activation [122] Oleuropein showed an inhibitory effect against COX-2 over-expression in different tumor cell lines [130], but the most studied EVOO phenolic compound is undoubtedly its derivative HT. It was shown, for instance, that LPS-induced expression of COX-2 and thus PGE2 production were inhibited by HT pretreatment in human and mouse granulocytes, macrophages, and monocytes [66,100,[124][125][126][127]. Among the mechanisms involved in COX-2 suppression by HT, as well as by EVOO polyphenols extracts, the inhibition of NF-κB following MAPKs modulation is the most recognized [107].…”
Section: Inhibition Of Cox-2 and Prostaglandinsmentioning
confidence: 99%
“…Among the mechanisms involved in COX-2 suppression by HT, as well as by EVOO polyphenols extracts, the inhibition of NF-κB following MAPKs modulation is the most recognized [107]. In vivo, it was observed that HT suppressed COX-2-induced inflammation and PGE2 production in a carrageenan-induced rat paw edema model, although the efficacy was less than that of celecoxib and indomethacin [124]. The same outcome was observed in diet-dextran sodium sulfate (DSS) mice which developed chronic colitis, where olive oil supplemented with HT or with phenolic extracts (850 ppm), given to enrich normal diet, resulted to be more efficacious than olive oil in down regulating cytokines release like TNF-α, MAPKs, and NF-κB pathway activation and consequently iNOS and COX-2 expression [125,126].…”
Section: Inhibition Of Cox-2 and Prostaglandinsmentioning
confidence: 99%
“…COX-1, COX-2, and 12-LOX upregulation during inflammatory processes plays an essential role in inflammatory signaling pathways ( Gunaydin & Bilge, 2018 ). Control over inflammation is required to avoid excessive damage from the exaggerated immune response or conversion to chronic illness ( Yonezawa et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…12,18 HT was found to inhibit the development of inflammatory cascade following LPS and carrageenan injection through downregulating the levels of pro-inflammatory cytokines including tumor necrosis factor alpha (TNF-α), and interleukin-1β (IL-1β) and other inflammatory mediators, namely inducible nitric oxide synthase (iNOS), cyclooxygenase-2 (COX-2) along with their products including nitric oxide (NO) and prostaglandin E2 (PGE2), and nuclear factor kappa-B (NF-κB). 16,19…”
Section: Introductionmentioning
confidence: 99%